Thermo, Electrical and Structural Properties of Solid Electroyte Doped Bi2O3 Binary and Ternary Systems - Erden, Erkan; Acer, Semra Durmuş (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
In this study; production and characterization of Bi2O3 based solid electrolytes used in medium-temperature solid oxide fuel cells (IT-SOFC) were performed. Solid electrolyte samples were obtained using compounds Eu2O3, Dy2O3 and Bi2O3. Stable phase which can create the highest power density ?-Bi2O3 (cubic-fcc) was tried to be reached for IT-SOFC. X-ray diffractometry (XRD) and differential thermal analysis and thermal gravimeter (TG/DTA) with binary (Eu2O3-Bi2O3) and ternary (Eu2O3-Dy2O3-Bi2O3) powder materials were analyzed for crystal structure identification. Bi2O3-based compounds with the cubic structure have been identified in those composition regions ((Bi2O3)0,6(Eu2O3)0,3) and ((Bi2O3)1-x-y(Dy2O3)x(Eu2O3)y, 0.25???x???0.35, y=0,05). Four point measurement techniques were used for electrical characterization. The conductivity of the ternary system is higher than the conductivity of the binary system. The highest conductive sample is (Bi2O3)0,7(Dy2O3)0,25(Eu2O3)0,05 0.3 S/cm at 800 oC.